Concurrent functional-structural reorganization in brain networks of AVM patients: a functional and structural study - Zhu, Qinghui; Han, Heze; Ma, Li; Li, Ruinan; Li, Zhipeng; Li, Anqi; Zhang, Haibin; Yuan, Kexin; Wang, Chengzhuo; Zhang, Yukun; Zhang, Hongwei; Chen, Yu; et al. (Frontiers in Neurology, 2025)
BackgroundUnruptured cerebral arteriovenous malformations (AVMs) generally do not cause focal neurological deficits, prompting limited investigation into potential neurological changes associated with them.PurposeTo determine whether AVMs exhibit combined functional and structural reorganization using resting-state functional MRI (rs-fMRI) and diffusion tensor imaging (DTI).Study typeRetrospective study.Population44 AVM patients who underwent both rs-fMRI and DTI examinations as well as an equal number of age- and sex-matched healthy controls.SequenceFunctional alterations were assessed using amplitude of low-frequency fluctuation (ALFF) analysis and functional connectivity networks, while fiber alterations were examined through fractional anisotropy (FA) analysis and tract-weighted functional connectivity (TW-FC) analysis.AssessmentFunctional alterations were evaluated by ALFF and functional connectivity networks, analyzed by neuroimaging specialists. Structural alterations were assessed through FA and TW-FC analysis, performed by experienced radiologists.Statistical testsIndependent two-sample t-test and the Mann– Whitney U test were used to analyze the continuous variables. Chi-squared test was used to test the categorical variables. We used permutation test with family-wise error correction while setting the statistical threshold of p < 0.05 at the cluster level. Two-tailed statistical significance was set at p < 0.05.ResultsAVMs showed significant ALFF differences in 12 brain regions and altered functional connectivity networks compared to healthy controls (p < 0.05). Fiber connectivity and density were significantly reduced in AVM patients (p < 0.05). TW-FC analysis indicated significant differences across regions of interest (ROIs) between AVMs and healthy controls, suggesting integrated functional and structural reconfigurations (p < 0.05).Data conclusionThe study reveals significant functional and structural changes in AVM patients, particularly in the visual network (VN) and sensorimotor network (SMN). These alterations suggest compensatory mechanisms that may offset functional deficits, providing insights into AVM pathophysiology and potential strategies for optimizing treatment to mitigate functional impairments and promote recovery.